(untitled) (Foro de Educacion, 2025)
In the context of educational equity and balanced allocation of high-quality educational resources, the distribution of physical education (PE) teachers is a key factor in improving educational quality and reducing regional differences. This study examines the spatial allocation characteristics of school PE teachers at the basic education level in Xi’an, aiming to reveal overall spatial patterns and regional disparities. In this study, Xi’an City was selected as a case, and an evaluation index system was constructed using literature review and the entropy weight method. Furthermore, quantitative methods including the natural breaks classification method, Kriging interpolation, and spatial autocorrelation analysis were employed to examine the current status and spatial distribution characteristics of physical education teachers in primary and secondary schools in Xi’an. The results indicate a clear central-periphery gradient: resources are concentrated in central urban districts and become progressively scarce toward the suburbs. A positive global Moran’s I (0.268, Z=5.079, p<0.01) confirms significant clustering: high-value areas form contiguous clusters in the central city, while low-value clusters dominate in remote counties, with scattered high-low “island” and low-high “depression” patterns at transitional zones. We also observed that student-to-teacher ratios are much higher in the core city (indicating heavier teacher workloads) whereas suburban schools face high vacancy rates and lower proportions of specialized and fully-trained PE teachers, emphasizing rural–urban inequity in teacher quality. Based on these findings, we recommend targeted resource placement: increasing quotas and incentives in underserved suburban areas, enhancing rural educational infrastructure, and strengthening teacher training and mobility programs to promote balanced, high-quality development of educational resources.